Intensive exploration of the fuel characteristics of biomass and biochar from oil palm trunk and oil palm fronds for supporting increasing demand of solid biofuels in Thailand. (November 2022) - Kongto, Pumin; Palamanit, Arkom; Ninduangdee, Pichet; Singh, Yashvir; Chanakaewsomboon, Issara; Hayat, Asif; Wae-hayee, Makata
Abstract: This investigation explored the intensive characteristics of biomass and biochar from oil palm trunk (OPT) and oil palm fronds (OPF) for supporting the increasing demand of solid biofuels in Thailand. The characteristics of these samples were also compared to low grade sub-bituminous coal (LGSBC). The results indicate that converting OPT and OPF to biochar not only enhanced the fuel ratio and atomic ratios, but it also improved the energy content. The higher heating values (HHV) of OPT and OPF biochars were 26.92 and 28.05 MJ/kg. The fuel ratio, atomic ratio and HHV of biochars were better than those of LGSBC and biomass forms. Thermal decomposition and combustion characteristics of biomass and biochar from OPT and OPF were clearly different in N 2 and air atmospheres. The biomass and biochar from OPT and OPF had high contents of alkali elements, consequently their ashes had high concentrations of some oxides like SiO2 and K 2 O. Biomass and biochar ashes from OPT and OPF had low initial deformation temperature (IDT). The IDT of OPT biochar ash was the lowest (907 °C), while the IDT of ash from LGSBC was above 1500 °C. The slagging and fouling indexes of biochars were clearly different from the LGSBC and biomass forms. Therefore, biomass and biochar from OPT and OPF have potential for solid biofuel use, and they are promising for further upgrading and applications. The user needs to be concerned with ash related problems like ash fusion, slagging, and fouling during combustion of these solid biofuels.